Potentials of underutilized legumes in food security - Ayilara, Modupe S.; Abberton, Michael; Oyatomi, Olaniyi A.; Odeyemi, Olu; Babalola, Olubukola O. (Frontiers in Soil Science, 2022)
Adopting underutilized legumes in tackling food security is essential, especially in this era of climate change. Underutilized legumes are embedded with inherent potentials such as the ability to survive in extreme conditions (such as temperature, drought, pH, saline, etc.), high nitrogen-fixing potential, weed and disease control ability, and high nutrient status. Underutilized legumes can improve the yield of companion crops in an intercropping system and as a subsequent crop (due to their residual effects). They possess symbiotic and non-symbiotic organisms in their nodules, they also have different organisms in their bulk soil, rhizoplanes and rhizosphere, which can fix nitrogen, solubilize phosphorus or produce exudates which helps in improving plant growth. Also, they contain some phytochemicals, including alkaloids, saponin, amino acids, organic and inorganic minerals, and compounds that help improve human health and prevent diseases (Ajilogba and Babalola, 2019). Hence, this review focuses on the current status of underutilized legumes in food security, the mechanism of underutilized legumes in enhancing food security, the challenges associated with their usage, and the prospects to enhance their potential in improving food security.